Isolation of suberin from birch outer bark and cork using ionic liquids: A new source of macromonomers - Ferreira, Rui; Garcia, Helga; Sousa, Andreia F; Freire, Carmen S R; Silvestre, Armando J D; Rebelo, Luís Paulo N; Silva Pereira, Cristina (Industrial Crops and Products, 2012)
Cholinium hexanoate, a biocompatible and biodegradable ionic liquid, was recently demonstrated to efﬁciently and selectively extract suberin domains from cork, combining high extraction efﬁciency with isolation of a partial depolymerised material. In the present paper, we report a comparative study of the characterisation of suberin extracted from birch outer bark and from cork using cholinium hexanoate. It became apparent that both extracted suberin samples showed still a cross-linked nature, i.e. likely to be closely related to in situ suberin. Suberin samples were mainly constituted by oligomeric or polymeric structures in turn essentially composed by long chain hydroxyacids monomers. Their high thermal stability together with the oligomeric/polymeric nature, open new perspectives for suberin use as macromonomers in the development of bio-based polymeric materials. This also contributes for the valorisation of suberin rich agro-forest residues.
Keywords: Birch outer bark; Cholinium hexanoate ionic liquids; Cork; suberin